2021
DOI: 10.3390/geosciences11020048
|View full text |Cite
|
Sign up to set email alerts
|

Using Spatial Validity and Uncertainty Metrics to Determine the Relative Suitability of Alternative Suites of Oceanographic Data for Seabed Biotope Prediction. A Case Study from the Barents Sea, Norway

Abstract: The use of habitat distribution models (HDMs) has become common in benthic habitat mapping for combining limited seabed observations with full-coverage environmental data to produce classified maps showing predicted habitat distribution for an entire study area. However, relatively few HDMs include oceanographic predictors, or present spatial validity or uncertainty analyses to support the classified predictions. Without reference studies it can be challenging to assess which type of oceanographic model data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…For example, Pohjankukka et al, 2017 has shown that the metrics produced by non-spatial cross validation can be up to 40% more optimistic than those of spatial cross-validation. Similar results were reported by (Dolan et al, 2021;Ploton et al, 2020;Roberts et al, 2017).…”
Section: Spatial Cross-validation and Model Performancesupporting
confidence: 91%
“…For example, Pohjankukka et al, 2017 has shown that the metrics produced by non-spatial cross validation can be up to 40% more optimistic than those of spatial cross-validation. Similar results were reported by (Dolan et al, 2021;Ploton et al, 2020;Roberts et al, 2017).…”
Section: Spatial Cross-validation and Model Performancesupporting
confidence: 91%
“…Spatial autocorrelation (SAC) can help to address the issues mentioned above, at the same time not considering spatial autocorrelation may result in over-optimistic CV predictions. Similar to recent studies [17,[19][20][21]23,24,139,140], we showed that the conventional and commonly applied random 10-fold CV could not assess the model performance when spatial autocorrelation is present. In such cases, spatial-and cluster-blocking perform better.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies in terrestrial and marine spatial ML modeling showed that if the commonly used, non-spatial, random k-fold CV is used, the prediction performance is over-optimistic when SAC exists in the data. The magnitude of the spatial overfitting varies based on the degree of SAC among the training points, the environmental similarity among the regions, and the ML method used [17][18][19][20][21][22][23][24][25]. In order to address the influence of SAC, different CV schemes have been proposed; the most common are buffer distances among training locations [18,26,27], successive distances [28], leaving one training location out [19,29], and spatial block training.…”
Section: Introductionmentioning
confidence: 99%
“…RF is a modelling approach commonly used to predict the distribution of shelf and deep-sea benthic communities or biotopes (e.g. Du Preez et al, 2016;Cooper et al, 2019;Dolan et al, 2021;Goode et al, 2021;O'Brien et al, 2022), which has shown to perform as well as other predictive modelling techniques for benthic habitat mapping (Hasan et al, 2012;Robert et al, 2016). Random Forest builds a large number of trees using subsets of the data and the environmental variables, with each tree making a prediction and the final assignation being based on the majority (Breiman, 2001).…”
Section: Predictive Mappingmentioning
confidence: 99%